Religious Topic: The Effectiveness of Learning Media Based on Powerpoint - Hasjiandito, Akaat; Adiarti, Wulan; Wantoro, Wantoro (Indonesian Journal of Early Childhood Education Studies, 2015)
Assalamah Pre-school & Kindergarten as one of the early childhood institution seeks to develop an innovative learning model by using interactive learning CD developed by the teachers. The aim of this study was to determine the validity of the media developed by teachers and to know how big the effectiveness of instructional media used in the learning activities. The method used in this research is to use an experimental method that is pretest-posttest control group design to compare the learning achievement of children before and after being treated by using powerpoint-based learning and compared between the experimental group and the control group. The results from this study show that the media are declared valid. It is based on the data obtained from experts validator and material validator. The media used in teaching with religious themes in Assalamah Pre-school & Kindergarten Ungaran are not only valid but also effective in the learning activities, it can be seen from the improvement in learning outcomes for students, especially in kindergarten level B.How to citeHasjiandito, A., Adiarti, W. & Wantoro. (2015). Religious Topic: The Effectiveness of Learning Media Based on Powerpoint. Indonesian Journal of Early Childhood Education Studies, 4(2), 111-115. doi:10.15294/ijeces.v4i2.9465DOI 10.15294/ijeces.v4i2.9465